Beating Death by Dying. Suicide as an Exit Strategy in Wolfgang Herrndorf’s Arbeit und Struktur - RIETSCHEL, Zarah (Anafora, 2023)
This paper provides a textual analysis of Wolfgang Herrndorf’s Arbeit und Struktur regarding the connection between the autobiographical self’s decision to commit suicide and his diagnosis of a fatal brain tumor (glioblastoma). It shows that the repeated examinations and their results, as well as consulted statistics and self-conducted research, function as the so-called “decision resources” regarding the intention to commit suicide. They affect thereby the endurance as well as the question concerning an eligible date for the intended suicide. In addition to studying different reactions to the course of the disease using the method of close reading, this paper undertakes a parallelization of the expressed suicidal intention and the autobiographical self’s intensive work as forms of a coping strategy. Working, more precisely writing, acts primarily as a meaningful occupation, while the planned suicide functions as an “exit strategy” that is used as the last possible solution to fight the illness. While a variety of interdisciplinary discourses have always rejected ‘suicide’ as a self-determined decision, suicide due to illness experiences a historically persistent legitimation. This can also be observed in the studied text on the reactions of the autobiographical self’s social environment. The inevitable death in the face of medical diagnoses thus legitimizes suicide.